Mathematics Teachers’ Design of Numeracy Task in Geometry and Measurement Content - Amri, Mira Amelia; Purwanto, Purwanto; Muksar, Makbul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Geometry and measurement affect our daily lives, both personal and sociocultural. Geometry is one of the contents in numeracy taught at every level of education. This study aimed to determine mathematics teachers' design of numeracy tasks using geometry and measurement content. Ninety-three math problems were collected from mathematics teachers in 31 Padang Pariaman districts, West Sumatra, Indonesia. Teachers were given problem-posing tasks and then asked to design numeracy tasks. To analyze, the tasks were classified as solvable or unsolvable and then further divided into context use level and cognitive process level domains. The numeracy context (personal, sociocultural, and scientific) was also analyzed. The study found that the tasks created had varying levels of context utilization, ranging from zero to second-order context. Most of the activities proposed were at the comprehension level, with just a tiny number designated as thinking functions in terms of cognitive processes. Some teachers' draft numeracy tasks in geometry content are discussed further.